The Limits of Lending: Banks and Technology Adoption across Russia - Çagatay Bircan; Ralph de Haas (Center for Economic Studies and ifo Institute (CESifo), 2015)
We exploit historical and contemporaneous variation in local credit markets across Russia to identify the impact of credit constraints on firm-level innovation. We find that access to bank credit helps firms to adopt existing products and production processes that are new to them. They introduce these technologies either with the help of suppliers and clients or by acquiring external know-how. We find no evidence that bank credit also stimulates firm innovation through in-house R&D. This suggests that banks can facilitate the diffusion of technologies within developing countries but that their role in pushing the technological frontier is limited.
Keywords: D22; F63; G21; O12; O31; 330; credit constraints; firm innovation; technological change